PENGANTAR AWAL TENTANG DESAIN SIRKULAR: PENDEKATAN HOLISTIK TERHADAP KEHIDUPAN BERKELANJUTAN - Ratum, Arifpermana (EDUTECH, 2024)
Makalah ini memberikan pengantar yang komprehensif tentang desain sirkular, yang menyajikannya sebagai pendekatan holistik untuk kehidupan berkelanjutan. Desain sirkular menantang ekonomi linier tradisional "ambil, buat, buang" dengan mempromosikan model regeneratif di mana sumber daya terus digunakan kembali, dipulihkan, dan didaur ulang. Studi ini meneliti prinsip-prinsip utama seperti merancang untuk daya tahan, daur ulang, dan meminimalkan limbah di seluruh siklus hidup produk. Melalui analisis sistem sirkular, makalah ini menyoroti peran desain dalam mengurangi dampak lingkungan dan penipisan sumber daya, sekaligus mendorong ketahanan ekonomi dan kesejahteraan sosial. Selain itu, makalah ini membahas integrasi desain sirkular ke dalam berbagai industri, termasuk mode, teknologi, dan konstruksi, serta potensi praktik-praktik ini untuk merevolusi cara masyarakat mengonsumsi dan memproduksi. Dengan mengadopsi strategi sirkular, pendekatan ini berkontribusi pada mitigasi perubahan iklim, pengurangan limbah, dan pelestarian ekosistem alam. Makalah ini menyimpulkan bahwa desain sirkular menawarkan jalur yang layak menuju pencapaian tujuan pembangunan berkelanjutan, yang membutuhkan kolaborasi interdisipliner dan inovasi lintas sektor. Melalui lensa ini, desain sirkular muncul tidak hanya sebagai kerangka kerja desain praktis tetapi juga sebagai gerakan penting untuk masa depan yang berkelanjutan. This paper provides a comprehensive introduction to circular design, presenting it as a holistic approach to sustainable living. Circular design challenges the traditional linear economy of “take, make, dispose” by promoting a regenerative model where resources are continuously reused, recovered, and recycled. The study examines key principles such as designing for sustainability, recyclability, and minimizing waste throughout a product’s life cycle. Through a circular systems analysis, the paper highlights the role of design in reducing environmental impacts and resource depletion, while promoting economic resilience and social well-being. In addition, the paper discusses the integration of circular design into a range of industries, including fashion, technology, and construction, and the potential for these practices to revolutionize the way society consumes and produces. By adopting circular strategies, this approach contributes to climate change mitigation, waste reduction, and the preservation of natural ecosystems. The paper concludes that circular design offers a viable pathway towards achieving sustainable development goals, requiring interdisciplinary collaboration and innovation across sectors. Through this lens, circular design emerges not only as a practical design framework but also as a vital movement for a sustainable future. This paper provides a comprehensive introduction to circular design, presenting it as a holistic approach to sustainable living. Circular design challenges the traditional linear economy of “take, make, dispose” by promoting a regenerative model where resources are continuously reused, recovered, and recycled. The study examines key principles such as designing for sustainability, recyclability, and minimizing waste throughout a product’s life cycle. Through a circular systems analysis, the paper highlights the role of design in reducing environmental impacts and resource depletion, while promoting economic resilience and social well-being. In addition, the paper discusses the integration of circular design into a range of industries, including fashion, technology, and construction, and the potential for these practices to revolutionize the way society consumes and produces. By adopting circular strategies, this approach contributes to climate change mitigation, waste reduction, and the preservation of natural ecosystems. The paper concludes that circular design offers a viable pathway towards achieving sustainable development goals, requiring interdisciplinary collaboration and innovation across sectors. Through this lens, circular design emerges not only as a practical design framework but also as a vital movement for a sustainable future.